Ophthalmological manifestations of hereditary transthyretin amyloidosis - Gondim,Francisco de Assis Aquino (2022)
ABSTRACT Transthyretin familial amyloidosis is the most common form of inherited systemic amyloidosis worldwide. The condition develops secondary to more than 100 different point mutations in the transthyretin gene (18q12.1). The mutations lead to abnormal amyloid deposits, mainly in the heart and peripheral nerves. Leptomeningeal and mainly ocular involvement is common. Although there are several different types of treatment available, ocular involvement, which occurs also in liver transplant recipients, remains a major challenge, progressing even in liver transplant recipients. Patients with ocular involvement require efficient ophthalmological follow-up to prevent vision loss. In this review, different forms of ocular involvement characterizing the subtypes of transthyretin mutations were described, and the effects of different treatments were summarized. Further research is necessary to fully elucidate these issues.